Limiting values of the 15N chemical shift of the imidazole ring of histidine at high pH - Vila, Jorge Alberto (2012)
Tautomeric identification by direct observation of 15N chemical shifts of the imidazole ring of histidine (His) has become a common practice in NMR spectroscopy. However, such applications require knowledge of the "canonical"? limiting values of the 15N chemical shift of the imidazole ring of His in which each form of His, namely, the protonated (H+) and the tautomeric Nε2 - H and N δ1 - H forms, respectively, is present to the extent of 100%. So far, the adopted canonical limiting values of the 15N chemical shift have been those available from model compounds. Whether these canonical values reflect those of the individual pure forms of His is investigated here by carrying out an analysis of the second-order shielding differences, ΔΔ = |Δε - Δδ |, with Δζ (ζ = ε or δ) being the density functional theory (DFT)-computed average shielding differences between the two nitrogens of the imidazole ring of His in each pure tautomeric form. In the high-pH limit, the results indicate that (i) the ΔΔ values from the DFT-computed shielding, but not from the commonly used canonical limiting values, are in closer agreement with those obtained with experimental chemical shift data from model compounds in solution and solid-state NMR; and (ii) the commonly used canonical limiting values of the 15N chemical shifts lead to an average tautomeric equilibrium constant that differs by a factor of ∼2.6 from the one computed by using DFT-based 15N limiting values, raising concern about the practice of using canonical limiting 15N values. This can be avoided by reporting tautomeric equilibrium constants computed by using only limiting 15N values for the N ε2 - H tautomer.